Two new species with tiny flowers for the genus Racinaea (Bromeliaceae) - Gouda, Eric J. (Phytotaxa, 2025)
Two new species of Racinaea are described and illustrated. Diagnoses against their most morphologically similar taxa and illustrations are provided. One of the new taxa is only known from Colombia and the other one from Peru.